Redistribution Dilemmas and Ethical Commitments: Advisers in Austerity Britain's Local Welfare State. Issue 1 (1st January 2022) - Forbess, Alice
ABSTRACT: Situated in Cameron's 'austerity Britain', this article explores contestations surrounding financial responsibility and fair redistribution in a local authority office and an NHS psychiatric hospital. Bureaucratic action is informed by simultaneously ethical and economic calculations, but to enact public good values, bureaucrats must circumvent material contingencies beyond their control. There is an ethical, even utopian, pressure upon street bureaucrats in local offices of the welfare state to deliver a fair outcome in the interests of all. At the same time, this is rendered increasingly difficult by austerity regimes which erode resources. This article examines how legal-style advice is used to handle such tensions. Advice is an interface that can convert economic value into moral legitimacy and vice versa. This ethnography explores advisers' 'ethical fixes', which aim to enable the system to operate more fairly, and the new forms of inequality which, paradoxically, emerge from actions motivated by ideals of universal equality.